Productive Development Policies in Latin America and the Caribbean: The Case of Mexico - Veronica Baz; Maria Cristina Capelo; Rodrigo Centeno; Ricardo Estrada (Inter-American Development Bank (IDB), 2010)
While Mexico has potential to grow rapidly, its economic growth has remained low for the past three decades. There is no consensus on the countrys development path or on how to achieve specific goals. Since the policy debate remains ideological and lacks pragmatism, productive development policies (PDPs) are often uncoordinated, redundant or even incongruent with each other. It is therefore important to understand the process whereby PDPs are designed and the institutional setting in which they are are implemented. This paper consequently examines whether PDPs respond to market failures and/or government failures. When PDPs are not designed to address specific market failures they can produce unwanted results or prove completely ineffective. When PDPs do address government failures, it is important to determine the reasons why the failure cannot be corrected in the first place and whether PDPs will be effective at addressing the problem in a second-best manner.
Keywords: O25; O43; 330; Industrial Policy; Institutions; Policymaking; Mexico